Macapat as a Model and Method of Learning English-Javanese Vocabulary - Wahyudi, Teguh Tri (KnE Social Sciences, 2017)
The purpose of this article is to offer Macapat as a model of learning English-Javanese vocabulary. Macapat is a kind of poetic meter in traditional Javanese poetry and is also known as a popular culture in Javanese society. In the formal education, from elementary until high degree, macapat is used as a lesson material in the college. Related with cross-cultural studies, the use of attractive model can give more experience for language learners and language teachers. For the learner, they can get more knowledge about macapat song and vocabulary. According to Javanese teacher competence, they must have mardawa basa, mardawa sastra and mardawa lagu, as a primary knowledge to compose language using poetic meter and also sing macapat. The teacher can improve their language competence to create a macapat song which is composed of two different vocabulary languages. It can be concluded that macapat can be used as a model of learning English-Javanese vocabulary. Keywords: Macapat, cross-cultural, English-Javanese vocabulary.